Drug Repurposing Approach Identifies Inhibitors of the Prototypic Viral Transcription Factor IE2 that Block Human Cytomegalovirus Replication - Giulio Nannetti (Cell Chemical Biology, 2016)
New targets for antiviral strategies are needed against human cytomegalovirus (HCMV), a major human pathogen. A cell-based screen aimed at finding inhibitors of the viral transcription factor Immediate-Early 2 (IE2) was performed in HCMV-infected cells expressing EGFP under the control of an IE2-inducible viral promoter. Screening of a library of bioactive small molecules led to the identification of several compounds able to inhibit EGFP expression and also HCMV replication with potency in the low-micromolar range. Follow-up studies with four selected hits indicated that they all block viral DNA synthesis as well as viral Early and Late gene expression. Furthermore, mechanistic studies confirmed that the compounds specifically act via inhibition of IE2 transactivating activity, thus blocking viral Early gene expression and the progression of virus replication. These results provide proof of concept for identifying small molecules that modulate the activity of a microbial transcription factor to control pathogen replication.